TEKNIK PENGEMASAN DALAM TRANSPORTASI UNTUK MEMPERTAHANKAN MUTU BUNGA POTONG ALPINIA (Alpinia purpurata) - Tri Marsetyowati (Widyariset, 2014)
Alpinia purpurata flower is one type of cut flower with great opportunity as an exported flower for its attrac- tive shapes and colors. In order to gain maximum benefit from cut flowers as ornaments, post-harvest treatments require attention. One of those treatments is packing which aims to maintain the quality of cut flowers during transport or shipping. The objectives of this study were to determine the type of primary packaging material and the most suitable placement inside the packaging during transport in order to conserve the quality. Factorial Completely Randomized Design with 3 replications was used. To find out the effects of the treatments, analysis of variance was done using F-test. Difference among treatments was tested using LSD at 5% significance level. The results showed that the use of PP plastic as packaging material gave a significant difference on weight loss, flowers’ freshness during transport, freshness period during demonstration time and the amount of holding solution absorbed. Packaging technique with plastic as the packaging material gave the best result with longer freshness period (7.77 days), flowers had the lowest weight loss (0.71%), the flowers seemed quite fresh (score of 4) and were able to absorb more holding solution (4.81ml/stalk/day) during demonstration time and therefore they remained in fresh condition. One-way orientation of placement was the best treatment at weight loss (0.77%) and the amount of holding solution absorbed (5.04ml/stalk/day).